Implementation of Digital Marketing E-Commerce in Innovative Products of Processed Squid as a Business Opportunity in Lamu Village - Hapsawati Taan; Herinda Mardin; Nur Mustaqimah (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
It is commonplace that nowadays a housewife becomes a business actor and only deals with gadgets without having a physical store with only gadgets and knowledge of e- commerce to market her selling products. With the many benefits of using e-commerce, e-commerce training was carried out to market innovative products processed by squid as a business opportunity for fishermen housewives in Lamu village, Batudaa Pantai sub-district, Gorontalo Regency. The stages in this activity include observation and interviews, activity planning, implementation, and the output is a marketplace account that has been created by activity participants. The implementation of the activity was divided into 2 sessions, namely session 1 providing material related to the general description of e-commerce and session 2 conducting hands-on practice on creating a marketplace accompanied by a community service team. The e-commerce training by creating a marketplace account and selling processed squid products for fishermen housewives was successfully carried out and received great appreciation and enthusiasm from the participants and the government of Lamu village. This is a business opportunity for fishermen housewives as well as adding knowledge and insight for participants to use e-commerce in selling processed squid products.